The present and future of neural interfaces - Valeriani, Davide; Santoro, Francesca; Ienca, Marcello (Frontiers in Neurorobotics, 2022)
The 2020s decade will likely witness an unprecedented development and deployment of neurotechnologies for human rehabilitation, personalized use and cognitive or other enhancement. New materials and algorithms are already enabling active brain monitoring, and are allowing the development of biohybrid and neuromorphic systems that can adapt to the brain. Novel brain-computer interfaces (BCIs) have been proposed to tackle a variety of enhancement and therapeutics challenges, from improving decision making to modulating mood disorders. While these BCIs have generally been developed in an open-loop modality to optimize their internal neural decoders, this decade will increasingly witness their validation in closed-loop systems that are able to continuously adapt to the user’s mental states. Therefore, a proactive ethical approach is needed to ensure that these new technological developments go hand in hand with the development of a sound ethical framework. In this perspective article, we summarize recent developments in neural interfaces, ranging from neurohybrid synapses to closed-loop BCIs, and thereby identify the most promising macro-trends in BCI research, namely simulating vs. interfacing the brain, brain recording vs. brain stimulation, hardware vs software technology etc. Particular attention is devoted to central nervous system interfaces, especially those with application in healthcare and human enhancement. Finally, we critically assess the possible futures of neural interfacing and analyze the short- and long-term implications of such neurotechnologies.